Hybrid manufacturing and mechanics of copper-based architected materials and copper–aluminum interpenetrating phase composites - Abdulrahman Jaber; Agyapal Singh; Dimitrios C. Rodopoulos; Nikolaos Karathanasopoulos (Journal of Materials Research and Technology)
The work investigates the thermomechanical performance of copper-based architected metamaterials and Copper–Aluminum Interpenetrating Phase Composites (IPCs) engineered through hybrid casting manufacturing methods. Triply periodic minimal surface (TPMS) Gyroid and IWP sheet- and solid-based metamaterials are fabricated and analyzed for their mechanical performance and thermal conductivity. In particular, architected CuCrZr alloy lattices with feature sizes as low as ∼320 μm, smooth surface finishes, and high-fidelity inner architected topologies are engineered. It is observed that sheet-based, single-phase architectures allow for substantially enhanced stiffness, specific strength, and effective heat conductivity attributes, compared to equal-weight, solid TPMS designs. Moreover, IWP-based, CuCrZr–AlSi10Mg IPCs with superior load-bearing capacities are engineered (up to ∼420 MPa), along with Gyroid-based IPCs, furnishing exceptional energy absorption attributes (toughness ∼105 MJ/m3). Their high specific energy absorption (up to ∼23 kJ/kg) is combined with extraordinary effective thermal conductivity values (∼280 W/m·K), attributes highly desirable in applications requiring combinations of high strength and efficient heat dissipation. The findings highlight the effectiveness of hybrid manufacturing techniques in the engineering of architected materials and IPCs, laying the foundation for the development of a novel class of multifunctional, architected advanced materials, with thermomechanical attributes beyond the performance range of available designs.